Innovative Solutions in Last Mile Logistics Assessment of the Feasibility of Large Retailers to Implement Crowdshipping - Garnbratt, Anna; Lindh, Casper (My University, 2024)
The surge in online shopping, fueled by advancements in technology and recent global events like the COVID-19 pandemic, has drastically changed how consumers shop. With the rise in demand for fast and sustainable deliveries, retailers are exploring new solutions, such as crowdshipping. While previous research has focused on optimizing crowdshipping operations and understanding why people participate, there's still a gap in understanding how feasible and practical it is for retailers. This study dives into crowdshipping's potential for retailers to improve their delivery strategies while being environmentally conscious. Through a mix of research methods, including a literature review, interviews and a case study with IKEA, we found that while crowdshipping can cut costs and reduce environmental impact, it's tricky to implement in a way that doesn't create more delivery trips. A retailer looking to utilize crowdshipping to improve challenges of last mile related activities must identify the strategy that leverages the benefits of crowdshipping whilst mitigating the risks and downfalls, which depends on the company’s resources and capabilities, as well as the conditions in the market environment. This study sheds light on the real-world challenges and opportunities of crowdshipping for retailers, providing valuable insights for improving delivery logistics in today's fast-paced e-commerce world.
Keywords: Crowdshipping; Last-Mile Logistics; E-Commerce; Retail Solutions; Implementation Strategy